PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT ALAM BERDIKARI MANDIRI - Ajeng Putri Triandana, Alifia; Ratnawati, Whina (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of competency and work discipline on employee performance at PT Alam Berdikari Mandiri. This type of research method uses a quantitative approach with a descriptive type. The population in this study is 53 people. The sampling technique that will be used is a non-probability sampling technique with a saturated sample type or often called a census, where the entire population is sampled as 53 employees. The analysis used includes: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, coefficient of determination analysis, t test and f test. The results of this research are based on statistical data analysis, the indicators in this research are valid and reliable. The results of this research show that Competence (X1) has a positive and partially significant effect on Employee Performance at PT Alam Berdikari Mandiri. It can be shown that the calculated t value is 4.383 > t table of 2.009 with a significance level < sig. 0.05 means that H0 is rejected and H1 is accepted, Work Discipline (X2) has a partially positive and significant effect on Employee Performance at PT Alam Berdikari Mandiri. It can be shown that the calculated t value is 4.710 > t table of 2.009 with a significance level < sig. 0.05 means that H0 is rejected and H2 is accepted, Competence (X1) and Work Discipline (X2) have a positive and significant effect simultaneously on Employee Performance at PT Alam Berdikari Mandiri which can be shown where the value of Fcount>Ftable or (54.485> 3.183) with a value level significance < sig. 0.05 or (0.000 < 0.05) means that H0 is rejected and H3 is accepted. Competence has a partially positive and significant effect on employee performance at PT Alam Berdikari Mandiri which can be shown where tcount>ttable or (4.383 > 2.009) with a significance level of <0.05 (0.000 <0.05) meaning that H01 is rejected and Ha1 is accepted. Work Discipline has a partially positive and significant effect on Employee Performance at PT Alam Berdikari Mandiri which can be shown where tcount>ttable or (4.710 > 2.009) with a significance level of <0.05 (0.000 <0.05) meaning that H02 is rejected and Ha2 is accepted, with the regression equation obtained Y = 7.834 + 0.366 X1 + 0.456 X2 and the simultaneous contribution of influence was 68.5% while the remainder (100% - 68.5%) = 31.5% was influenced by other factors not included in the research.